Detection of diketopiperazine and pyrrolnitrin, compounds with anti-Pythium insidiosum activity, in a Pseudomonas stutzeri environmental strain - Thongsri, Yordhathai; Aromdee, Chantana; Yenjai, Chavi; Kanokmedhakul, Somdej; Chaiprasert, Angkana; Hamal, Petr; Prariyachatigul, Chularut (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2014)
AIMS: Screening of bacterial flora for strains producing metabolites with inhibitory effects on the human pathogenic oomycete Pythium insidiosum. Separation and characterization of extracts from Pseudomonas stutzeri with anti-Pythium inhibitory activity. Search for genes with anti-Pythium effect within the genome of P. stutzeri. METHODS: A total of 88 bacterial strains were isolated from water resources in northeastern Thailand. Two screening methods were used to establish their inhibitory effects on P. insidiosum. One strain, P. stutzeri ST1302 was randomly chosen, and the extract with anti-P. insidiosum activity was fractionated and subfractionated using liquid column chromatography and purified by thin layer chromatography. The chemical structure of purified fractions was determined by Fourier transform infrared spectroscopy, nuclear magnetic resonance and mass spectrometry. Further, search for genes involved in the anti-Pythium activity (phenazine-1-carboxylic acid, 2,4-diacetylphloroglucinol, pyoluteorin and pyrrolnitrin) was undertaken in this P. stutzeri strain using primers described in the literature. RESULTS: Anti-P. insidiosum activity was detected in 16 isolates (18.2%). In P. stutzeri ST1302, a subfraction labeled PYK7 exhibited strong activity against this oomycete. It was assigned to the diketopiperazines as cyclo(D-Pro-L-Val). In the search for genes, one gene region was successfully amplified. This corresponded to pyrrolnitrin. The results suggest the possibility of using the related metabolites against P. insidiosum. This is the first report on the inhibitory effects of P. stutzeri against this oomycete. The results may contribute to the development of antimicrobial drugs/probiotics against pythiosis.
Keywords: Genome, Bacterial; Thailand; Pseudomonas stutzeri; pythióza; Pyrrolnitrin; genom bakteriální; Pythium; mikrobiální testy citlivosti; Microbial Sensitivity Tests; Pythiosis; Thajsko; Diketopiperazines; diketopiperaziny; pyrrolnitrin